When is it good to feel bad? How sadness and fear differ in their effects on routine development - Stumpf-Wollersheim, Jutta; Oehler, Patrick J.; Rimbeck, Marlen; Spörrle, Matthias; Welpe, Isabell M. (Frontiers in Psychology, 2023)
This study follows recent calls to explore the emotional foundations of routine development. Routine development forms a nexus between stability and change and is thus crucial for studying organizational decision-making and organizational change. Individuals and teams going through organizational change often experience sadness and fear. Against this background, we conducted a laboratory experiment with 84 teams to study the effect of sadness and fear on routine development. In the sadness condition, we observed positive effects on repetitiveness, speed, reliability, and attentiveness in action. Teams experiencing fear reacted better to ‘performance traps’ in which pre-established routines are ineffective. Our findings show how the behaviors elicited by sadness and fear might ultimately affect team behavior, and therefore managerial practices.